Delay And Treatment of Infectious Mononucleosis in Children - Mahamadzhonov Islombek Abdurasul Ugli (Academia Open, 2025)
General Background: Infectious mononucleosis (IM) caused by Epstein–Barr virus (EBV) is a common childhood infection that can lead to complications when diagnosis and treatment are delayed. Specific Background: Pediatric IM often shows atypical symptoms resembling other viral illnesses, causing frequent diagnostic delays. Knowledge Gap: There is limited evidence on how such delays affect disease severity and recovery in children. Aims: This study examined the relationship between diagnostic and treatment delays and clinical outcomes in pediatric IM. Results: Children diagnosed more than 10 days after symptom onset had longer recovery, more hepatic and lymphoid complications, and higher inflammation than those diagnosed early. Novelty: The study reveals a clear link between diagnostic delay and poorer outcomes in pediatric EBV infections. Implications: Early diagnosis and standardized management are essential to prevent complications and improve recovery in infected children. Highlight : Delay in diagnosis leads to prolonged illness and higher complication rates in children. Early diagnosis and treatment improve recovery and reduce systemic inflammation. Highlights the need for standardized pediatric diagnostic and treatment guidelines Keywords : Infectious mononucleosis, Epstein-Barr virus, diagnostic delay, pediatric infection, early treatment